1968
DOI: 10.1113/jphysiol.1968.sp008560
|View full text |Cite
|
Sign up to set email alerts
|

A down then up staircase in frog ventricle due to altered excitation—contraction coupling

Abstract: SUMMARY1. Repetitive stimulation of frog ventricle strips bathed in low calcium (< 1mM) fluids produced a decrease followed by an increase in successive tension responses which was not due to changes in the amplitude or the duration of the cardiac action potential.2. The depression of contraction reached its peak 5-10 sec after a conditioning contraction and decayed to one half in about 0 5 min; it was greater during a series of 5-10 stimuli when the frequency was increased from 3/min to 12/min.3. Lowering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…They found that the twitch tension staircase is negative (up to -60% in magnitude) for periods of 1 to 3 min at heart rates that do not shorten the action potential duration. We found that the rate threshold for the onset of cumulative [Ca"+o depletion is surprisingly similar to that for the negative tension staircase, i.e., 1 beat per minute (Brown and Orkand, 1968). This initial negative tension staircase may be in fact a result of the [Ca"+], depletions we have measured in this preparation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…They found that the twitch tension staircase is negative (up to -60% in magnitude) for periods of 1 to 3 min at heart rates that do not shorten the action potential duration. We found that the rate threshold for the onset of cumulative [Ca"+o depletion is surprisingly similar to that for the negative tension staircase, i.e., 1 beat per minute (Brown and Orkand, 1968). This initial negative tension staircase may be in fact a result of the [Ca"+], depletions we have measured in this preparation.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, frog ventricular twitch tension rapidly responds to changes in the superfusate [Ca++] (Kavaler et al, 1978). Brown and Orkand (1968) have studied the frog ventricular isometric twitch tension response to increased heart rates in the range of [Ca +]o studied here. They found that the twitch tension staircase is negative (up to -60% in magnitude) for periods of 1 to 3 min at heart rates that do not shorten the action potential duration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Niedergerke (1956) and Brown & Orkand (1968) attribute 'staircase' effects in the frog ventricle to changes in excitation-contraction coupling. This view is supported by the finding that no changes took place in the action potential amplitude or duration.…”
Section: Slow Inward Current Facilitation Discussionmentioning
confidence: 99%
“…6a) or included a portion of very shallow rise or even a decline of tension (cf. Brown & Orkand, 1968). These features and others, e.g.…”
mentioning
confidence: 99%
“…In these, tension changes were examined over a range of tension usually not much above the level of the line DC in Fig. 2 b so as not to exceed the region of the steepest rise in each of the 'dose-action' curves, but also not below the level BA to avoid complex effects which occur when the heart rate or calcium concentration, or both, are low, as described recently by Brown & Orkand (1968). The experiments were also limited to the period after the initial 1-2 hr of perfusion was over and heart ventricles had passed into the hypodynamic condition.…”
mentioning
confidence: 99%